A Review on Fat Necrosis of the Breast: The Dilemma of Differential Diagnosis with Cancer - Toktam Beheshtian; Asiie Olfatbakhsh (Archives of Breast Cancer, 2015)
Fat necrosis is a benign inflammatory process which can involve adipose tissue anywhere in the body. A previous history of trauma or surgery may or may not be present. Information about the clinical and radiological appearance of this lesion is very important because it can mimic breast cancer.